[Pt2(μ-S)2(PPh3)4] as a metalloligand toward main-group Lewis acids. A "mexican-hat-like" structure for [Pt2Tl(μ3-S)2(PPh3)4]X (X = NO3, PF6) with a two-coordinate angular Tl(I) - Zhou, M. (2014)
Inorganic Chemistry